Intervention and Co-Creation: Art-Led Transformation of Spatial Practices and Cultural Values in Rural Public Spaces - Peiyuan Li; Wencui Zhang (Land)
Amid the accelerating processes of modernization and commercialization, traditional rural public spaces are increasingly losing their cultural value and social functions. This study investigates the transformative role of art intervention in enhancing the quality and cultural significance of rural public spaces, with a focus on Machang Village in Tengchong, China. The study first develops a conceptual model to explore the causal relationships and pathways between these influencing factors. Drawing on this framework, the research then uses Structural Equation Modeling (SEM) to empirically test a multi-dimensional resident satisfaction model that incorporates spatial aesthetics, functional suitability, historical-cultural identity, and emotional cognition. Through field surveys and data collected from 224 residents, the study reveals that cultural emotions and functional completeness are the most influential factors in driving overall satisfaction. Artistic innovation and aesthetics contribute moderately, indicating that visual creativity alone is insufficient without deeper cultural integration and functional coherence. The findings suggest a dual-pathway satisfaction mechanism, where both symbolic emotional resonance and practical usability shape residents’ perceptions of public space quality. The study offers theoretical and practical insights into optimizing rural public space design, advocating for art-led, community-engaged, and culturally embedded approaches to rural revitalization.